(untitled) (Bangladesh Journal of Dental Research & Education, 2015)
This case report presents restoration of an endodontically treated carious broken mandibular first molar with divergent roots, restored with split-cast post and core fabricated by direct technique. Endodontic treatment of a mutilated tooth may prove unfruitful if it is not well restored to bear the forces of occlusion. So the options of prosthetic reconstruction should be well considered before attempting endodontic treatment on badly broken teeth. In such cases post is the choice of restoration as it serves to retain core. Badly broken molar was preserved by using multiple posts in the divergent canals. Non parallel accessory posts was used as it increased the retentive surface area of the cast post and core, minimized the chance of root perforation during tooth preparation and also redistribute the forces of occlusion. An ideal post system should have the ability to distribute the functional stresses evenly along the root surface and produce minimal stress during placement and cementation. The clinician should select the right type of post and core system considering the biological, mechanical and esthetic needs for each individual tooth. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22460 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 33-35